2020
DOI: 10.1186/s13578-020-00394-3
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profile in blood according to ischemic stroke etiology

Abstract: Background: The discovery of novel biomarkers of stroke etiology would be most helpful in management of acute ischemic stroke patients. Recently, circular RNAs (circRNAs) have been proposed as candidate biomarkers of neurological conditions due to its high stability. circRNAs function as sponges, sequestering miRNAs and are involved in most relevant biological functions. Our aim was to identify differentially expressed circRNAs in acute ischemic stroke patients according to stroke etiology. Methods: A comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
(60 reference statements)
2
31
0
Order By: Relevance
“…Studies have recently been conducted in the field of stroke regarding the use of RNA in peripheral blood (136). These studies are supported by clinical applications in the diagnosis of diseases, such as myocardial infarction (137) and cancer (138).…”
Section: Transcriptome Profiling Of Monocyte/macrophage In Ischemic Smentioning
confidence: 99%
“…Studies have recently been conducted in the field of stroke regarding the use of RNA in peripheral blood (136). These studies are supported by clinical applications in the diagnosis of diseases, such as myocardial infarction (137) and cancer (138).…”
Section: Transcriptome Profiling Of Monocyte/macrophage In Ischemic Smentioning
confidence: 99%
“…AGO2 is associated with the miRNA pro le in the brain of a rat stroke model [61]. AGO2, FUS, HuR and EIF4A3 were reported to have potential roles in IS [21], but their roles in ICH have never been reported. FMR1 and U2AF2 are involved in human neural cells and regulates the development of neural cells [62], DGCR8 is involved in the development of neuropsychiatric disorders and glioma cells [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics make circRNAs promising biomarkers in many human diseases [14]. In the stroke eld, circRNA expression pro le changes in IS have been described, supporting circRNAs as potential biomarkers and therapeutic targets in IS [21][22][23][24][25]. Additionally, two recent studies revealed that the circRNA expression pro les signi cantly changed after ICH in rat brain tissues [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations